Capital Account Liberalization : What Do Cross-Country Studies Tell Us? - Eichengreen, Barry (World Bank, Washington, DC, 2014)
Capital account liberalization, it is fair to say, remains one of the most controversial and least understood policies of our day. One reason is that different theoretical perspectives have very different implications for the desirability of liberalizing capital flows. Another is that empirical analysis has failed to yield conclusive results. The answer, another influential strand of thought contends, is that this efficient-markets paradigm is fundamentally misleading when applied to capital flows. Limits on capital movements are a distortion. It is an implication of the theory of the second best that removing one distortion need not be welfare enhancing when other distortions are present.